Effects of short duration stress management training on self-perceived depression, anxiety and stress in male automotive assembly workers: a quasi-experimental study - Naing L; Rusli BN; Edimansyah BA (Journal of Occupational Medicine and Toxicology, 2008)
Abstract To examine the effects of short duration stress management training (SMT) on self-perceived depression, anxiety and stress in male automotive assembly workers, 118 male automotive workers from Pekan, Pahang (n = 60, mean age = 40.0 years, SD = 6.67) and Kota Bharu, Kelantan (n = 58, mean age = 38.1 years, SD = 5.86) were assigned to experimental and control group, respectively. A SMT program consisting of aerobic exercise, stress management manual, video session, lecture, question and answer session, and pamphlet and poster session were conducted in the experimental group. A validated short-form Malay version of the Depression Anxiety Stress Scales (DASS-21) were self-administered before and after the intervention program in the experimental and control group and their time and group interaction effects were examined using the repeated measure ANOVA test. Results indicated that the mean (SD) scores for DASS-Depression (p = 0.036) and DASS-Anxiety (p = 0.011) were significantly decreased, respectively, after the intervention program in the experimental group as compared to the control group (significant time-group interaction effects). No similar effect was observed for the mean (SD) scores for DASS-Stress (p = 0.104). However, the mean (SD) scores for subscales of DASS-Depression (Dysphoria, p = 0.01), DASS-Anxiety (Subjective Anxiety, p = 0.007, Situational Anxiety, p = 0.048), and DASS-Stress (Nervous Arousal, p = 0.018, Easily Upset, p = 0.047) showed significant time and group interaction effects. These findings suggest that short duration SMT is effective in reducing some aspects of self-perceived depression, anxiety and stress in male automotive workers.